Efficient Pollution Regulation: Getting the Prices Right - Muller, Nicholas Z.; Mendelsohn, Robert (American Economic Review, 2009)
This paper argues for efficient environmental regulations that equate the marginal damage of pollution to marginal abatement costs across space. The paper estimates the source-specific marginal damages of air pollution and calculates the welfare gain from making the current sulfur dioxide allowance trading program for power plants more efficient. The savings from using trading ratios based on marginal damages are between $310 and $940 million per year. The potential savings from setting aggregate emissions efficiently and from including more sources of air pollution are many times higher. (JEL H23, Q53, Q58)